Age and sex-specific stroke epidemiology in COVID-19 - Kim, Youngran; Parekh, Maria A.; Li, Xiaojin; Huang, Yan; Zhang, Guo-Qiang; Manwani, Bharti (Frontiers in Stroke, 2023)
Background: COVID-19 has emerged as an independent risk factor for stroke. We aimed to determine age and sex-specific stroke incidence and risk factors with COVID-19 in the US using a large electronic health record (EHR). Methods: A retrospective cohort study was conducted using individual-level data from Optum® de-identified COVID-19 EHR. A total of 387,330 individuals aged≥18 with laboratory-confirmed COVID-19 between March 1, 2020, to December 31, 2020, were included. The primary outcome was cumulative incidence of stroke after COVID-19 confirmation within 180 days of follow-up or until death. Kaplan-Meier cumulative incidence curves for acute ischemic stroke (AIS), intracerebral hemorrhage (ICH) and a composite outcome of all stroke were stratified by sex and age, the differences in curves were assessed using log-rank test. Relative risk of stroke by demographics and risk factors was estimated using multivariable Cox-proportional hazards regressions and adjusted hazard ratios (aHR). Results: Of 387,330 COVID-19 patients, 2,752 patients (0.71%, 95%CI 0.68-0.74) developed stroke during the 180-day follow-up, AIS in 0.65% (95%CI 0.62-0.67) and ICH in 0.11% (95%CI 0.10-0.12). 57% of strokes among COVID-19 patients occurred within 3 days. Advanced age was associated with substantially higher stroke risk with aHR 6.92 (5.72–8.38) for ages 65-74, 9.42 (7.74–11.47) for ages 75-84, and 11.35 (9.20–14.00) for ages 85 and older compared to age 18-44 years. Men had a 32% higher risk of stroke compared to women. African-American (aHR 1.78(1.61-1.97)) and Hispanic patients (aHR 1.48(1.30-1.69)) had increased risk of stroke compared to Whites. Conclusions: This study has several important findings. AIS and ICH risk in patients with COVID-19 is highest in the first 3 days of COVID-19 positivity; this risk decreases with time. The incidence of stroke in patients with COVID-19 is 0.65% for AIS and 0.11% in ICH patients, slightly lower than previously reported. Traditional stroke risk factors are associated with increased risk of stroke in patients with COVID-19. Male sex is an independent risk factor for stroke in COVID-19 patients across all age groups. African-American and Hispanic patients have higher risk of stroke from COVID-19.